Neuroretinitis Caused by Bartonella henselae (Cat-Scratch Disease) in a 13-Year-Old Girl - Teodoro Durá-Travé; Maria Eugenia Yoldi-Petri; Fidel Gallinas-Victoriano; Ana Lavilla-Oiz; Marta Bove-Guri (Hindawi Limited, 2010)
Cat-scratch disease-related neuroretinitis is a relatively unusual pathology, with suspicious clinical epidemiological and serological diagnosis. We present a case of an adolescent suffering from unilateral neuroretinitis associated with Bartonella henselae infection characterized by abrupt loss of vision, optic disc swelling, and macular star exudates with optimal response to antibiotic treatment.